2015
DOI: 10.4236/ajps.2015.610166
|View full text |Cite
|
Sign up to set email alerts
|

Induced Systemic Resistance in Two Genotypes of <i>Brassica napus</i> (AACC) and <i>Raphanus oleracea</i> (RRCC) by <i>Trichoderma</i> Isolates against <i>Sclerotinia sclerotiorum</i>

Abstract: Two different species, Trichoderma viride TV10 and Trichoderma harzianum TH12 from 30 Trichoderma isolates were selected out based on their high growth inhibition of the phytopathogen Sclerotinia sclerotiorum (Lib) de Bary, which reached 84.44% and 100%, respectively. Their untreated culture filtrates (CF) and culture filtrates treated with heat (CFH) also were tested for growth inhibition of the pathogen in potato dextrose agar (PDA). Morphological and molecular characterisation by internal transcribed spacer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Many studies have demonstrated that plant genotype can affect the expression of induced resistance mediated by biological (Martinelli et al, 1993;Korolev et al, 2008;Banani et al, 2014;Alkooranee et al, 2015;Hossain and Sultana, 2015;Prashar and Vandenberg, 2017;Samain et al, 2019;Adam, 2020) and chemical (Herman et al, 2007;Ishikawa et al, 2007;Sharma et al, 2010Sharma et al, , 2012Walters et al, 2011;Cordova-Campos et al, 2012;Banani et al, 2014;Pawlowski et al, 2016) inducers in a wide variety of crops. Therefore, it is not surprising that like Tucci et al (2011), we observed genetic differences in ISR by Trichoderma against Botrytis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that plant genotype can affect the expression of induced resistance mediated by biological (Martinelli et al, 1993;Korolev et al, 2008;Banani et al, 2014;Alkooranee et al, 2015;Hossain and Sultana, 2015;Prashar and Vandenberg, 2017;Samain et al, 2019;Adam, 2020) and chemical (Herman et al, 2007;Ishikawa et al, 2007;Sharma et al, 2010Sharma et al, , 2012Walters et al, 2011;Cordova-Campos et al, 2012;Banani et al, 2014;Pawlowski et al, 2016) inducers in a wide variety of crops. Therefore, it is not surprising that like Tucci et al (2011), we observed genetic differences in ISR by Trichoderma against Botrytis.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidence has suggested that resistance against necrotrophic pathogens could be modulated by the jasmonic acid/ethylene (JA/ET) signaling pathway [63,64,65,66]. Since S. sclerotiorum is a necrotrophic fungus, it is therefore likely that either the JA or ET signaling pathway might be involved in the resistance response of cabbage lines [67,68]. Another study also found a similar association between CYP81F2 expression and GBS levels in B. oleracea [69].…”
Section: Discussionmentioning
confidence: 99%
“…Control plants remained undisturbed, whereas mock-treatment was done with mycelium-free agar plugs. Two inoculation procedures described in Zhao and Meng [74,75] and Yu et al [67] were used, with modifications (Table S6), to assess resistance to S. sclerotiorum . The first procedure was inoculation of the third leaf of ninth-leaf-stage plants with mycelial agar plugs in a growth chamber, to evaluate leaf resistance.…”
Section: Methodsmentioning
confidence: 99%
“…After infection with Xcc, we quantified a decrease in the harmful effect of the bacteria on B. oleracea plants preinoculated with Trichoderma sp. The ability of different Trichoderma species to activate plant systemic resistance against different pathogens has been widely proven in various plant species 49 , including Brassica plants as B. napus with T. harzianum 50,51 or T. viride 52 , B. rapa with T. pseudokoningii 53 , and even B. oleracea var. capitate with T. harzianum against Rhizoctonia solani 54 .…”
Section: B Oleracea Accession Mbg-brs0426 Mbg-brs0106 Mbg-brs0292 Mbmentioning
confidence: 99%